Last Advances in Silicon-Based Optical Biosensors - Fernández Gavela, Adrián (Sensors (Basel), 2016)
We review the most important achievements published in the last five years in the field of silicon-based optical biosensors. We focus specially on label-free optical biosensors and their implementation into lab-on-a-chip platforms, with an emphasis on developments demonstrating the capability of the devices for real bioanalytical applications. We report on novel transducers and materials, improvements of existing transducers, new and improved biofunctionalization procedures as well as the prospects for near future commercialization of these technologies.